Influence of the snow–soil contact conditions on the depth of ground freezing (based on observations in the Kursk region) - V. M. Kotlyakov; A. V. Sosnovsky; R. A. Chernov (Лëд и снег)
The results of measurements of the ground freezing under a snow cover do not always agree with the calculations. The reason for this may be variability of thermal characteristics of the snow cover which properties depend on the landscape features. One of probable reasons may be also the incomplete contact between the snow cover and the soil. In autumn, the ground surface is usually covered with fallen leaves or withered grass. Estimates show that, in the presence of such layer on the soil surface, the air gap between snow and soil with the 1 cm thickness has a thermal protection capacity equal to the value of a 10‑centimeter thick layer of snow. Sometimes the presence of local gaps in the snow-soil interface can also be caused by other reason, for example, the spontaneous downfall of a depth hoar layer. The results of field measurements of snow cover characteristics, ground freezing depths and investigation of the contact conditions at the snow-soil interface carried out in different landscapes are presented. The results of mathematical modeling showed that when the air gap between snow and soil is taken into account the calculated values of depth of ground freezing are in a good agreement with data of the measurements. This consideration is especially important for small thicknesses of snow cover with high density and thermal conductivity. Numerical experiments did also show that the snow hardness is the necessary characteristic for analysis of the snow cover state. This provides more accurate estimating of the snow thermal conductivity that is closely connected with its hardness.